Bronchiectasis in indigenous and non‐indigenous residents of Australia and New Zealand. Issue 8 (4th March 2018) - Blackall, Sean R.; Hong, Jae B.; King, Paul; Wong, Conroy; Einsiedel, Lloyd; Rémond, Marc G.W.; Woods, Cindy; Maguire, Graeme P.
ABSTRACT: Background and objective: Bronchiectasis not associated with cystic fibrosis is an increasingly recognized chronic lung disease. In Oceania, indigenous populations experience a disproportionately high burden of disease. We aimed to describe the natural history of bronchiectasis and identify risk factors associated with premature mortality within a cohort of Aboriginal Australians, New Zealand Māori and Pacific Islanders, and non‐indigenous Australians and New Zealanders. Methods: This was a retrospective cohort study of bronchiectasis patients aged >15 years at three hospitals: Alice Springs Hospital and Monash Medical Centre in Australia, and Middlemore Hospital in New Zealand. Data included demographics, ethnicity, sputum microbiology, radiology, spirometry, hospitalization and survival over 5 years of follow‐up. Results: Aboriginal Australians were significantly younger and died at a significantly younger age than other groups. Age‐ and sex‐adjusted all‐cause mortality was higher for Aboriginal Australians (hazard ratio (HR): 3.9), and respiratory‐related mortality was higher for both Aboriginal Australians (HR: 4.3) and Māori and Pacific Islander people (HR: 1.7). Hospitalization was common: Aboriginal Australians had 2.9 admissions/person‐year and 16.9 days in hospital/person‐year. Despite Aboriginal Australians having poorer prognosis, calculation of the FACED score suggested milder disease in this group. Sputum microbiology varied with Aspergillus fumigatus more often isolated from non‐indigenous patients. Airflow obstruction was common (66.9%) but not invariable. Conclusions: Bronchiectasis is not one disease. It has a significant impact on healthcare utilization and survival. Differences between populations are likely to relate to differing aetiologies and understanding the drivers of bronchiectasis in disadvantaged populations will be key. Abstract : This study compares the nature and outcomes associated with bronchiectasis in adult indigenous and non‐indigenous populations in Australia and New Zealand. It highlights the disproportionate impact of bronchiectasis in terms of premature mortality and healthcare utilization for indigenous populations, particularly Aboriginal Australians. See related Editorial